1979
DOI: 10.1111/j.1471-0528.1979.tb10697.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF AN lNJECTABLE PROGESTOGEN CONTRACEPTIVE ON BLOOD COAGULATION AND FIBRINOLYSIS

Abstract: SummaryIn 26 women receiving either medroxyprogesterone acetate (Depo‐Provera) injections or combined oestrogen‐progestogen pills for contraception, tests of coagulation and fibrinolysis were performed before treatment, and after 8, 16 and 24 weeks of therapy. In the medroxyprogesterone group no significant changes were induced in fibrinogen, the vitamin K‐dependent factors, or antithrombin III. Plasminogen levels fell during therapy, and were significantly lower than pre‐treatment values after 16 and 24 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…The findings in this study disagrees with the findings of Mohamed et al, [13], who observed that there was no statistically significant difference in prothrombin time, activated partial thromboplastin time, platelet count, fibrinogen and antithrombin, between users of injectable contraceptives and non-users of contraceptives. Also, there was no agreement with the study carried out by Whigham et al, [14], where they observed no statistically significant differences in antithrombin and fibrinogen. Additionally, the findings in this study is at variance with that of Joseph et al, [15], where they reported no statistically significant difference in platelet counts, prothrombin time and activated partial thromboplastin time between contraceptives users and non-users.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The findings in this study disagrees with the findings of Mohamed et al, [13], who observed that there was no statistically significant difference in prothrombin time, activated partial thromboplastin time, platelet count, fibrinogen and antithrombin, between users of injectable contraceptives and non-users of contraceptives. Also, there was no agreement with the study carried out by Whigham et al, [14], where they observed no statistically significant differences in antithrombin and fibrinogen. Additionally, the findings in this study is at variance with that of Joseph et al, [15], where they reported no statistically significant difference in platelet counts, prothrombin time and activated partial thromboplastin time between contraceptives users and non-users.…”
Section: Discussioncontrasting
confidence: 76%
“…The total study population consists of Seventyfive (75) apparently healthy, non-pregnant, nonsmoking women, aged between 25 and 45years. Forty-five (45) women on either DEPO-PROVERA (31) or Implanon (14) served as the test subjects while thirty (30) apparently healthy non-pregnant women of the same age bracket who never used hormonal contraceptive or any other family planning method, constituted the control group.…”
Section: Study Populationmentioning
confidence: 99%
“…Oral contraceptives with the highest risks of venous thrombosis were also associated with the highest levels of SHBG and SHBG levels were positively associated with resistance to activated protein C. 15,16 Therefore, because SHBG levels have been seen as a potentially useful marker for the risk of venous thrombosis, a decrease in SHBG associated with injectable DMPA-only contraceptives, as reported by Walsh et al, 9 suggests that these contraceptives are not associated with an increased risk of venous thrombosis, contrary to our findings. However, other studies 8,17,18 on the effect of DMPA contraceptives showed little or no effect on coagulation or inflammation markers.…”
Section: Discussionmentioning
confidence: 98%
“…However, effects on the vessel wall by estrogens and progestogens have also been reported (4, 18), (19). Such effects may depend on the type and dose of the progestogen, the route of administration, the duration of exposure, and, when combined with estrogens, the type and dose of the estrogen (20), (21). It is disputed to what extent progestogens may affect primary hemostasis and platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%